2002
DOI: 10.1016/s0735-1097(02)01722-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic sinus and atrioventricular node electrophysiologic adaptations in endurance athletes

Abstract: Under double-pharmacologic blockade, we demonstrated that sinus automaticity and AV node conduction changes of endurance athletes are related to intrinsic physiology and not to autonomic influences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(124 citation statements)
references
References 25 publications
10
108
2
4
Order By: Relevance
“…Consequently, ACh does not seem to be implicated in the A-V conduction system refractoriness increase produced by physical training. These results are consistent with Stein et al (37), which found that atrioventricular node effective refractory period in athletes was longer than in untrained individuals even after pharmacological blockade, indicating that these changes were caused by intrinsic electrophysiological modifications. Neither physical training nor parasympathetic blockade modified retrograde conduction system refractoriness.…”
Section: Refractoriness and Parasympathetic Blockadesupporting
confidence: 92%
See 2 more Smart Citations
“…Consequently, ACh does not seem to be implicated in the A-V conduction system refractoriness increase produced by physical training. These results are consistent with Stein et al (37), which found that atrioventricular node effective refractory period in athletes was longer than in untrained individuals even after pharmacological blockade, indicating that these changes were caused by intrinsic electrophysiological modifications. Neither physical training nor parasympathetic blockade modified retrograde conduction system refractoriness.…”
Section: Refractoriness and Parasympathetic Blockadesupporting
confidence: 92%
“…These results are partially in accordance with those previously obtained in human (20,19,6,36,37) and experimental studies (28,27,38,39). Nevertheless, muscarinic receptor blockade with atropine did not modify the negative chronotropic and dromotropic effects produced by physical training.…”
Section: Effect Of Parasympathetic Blockade On Automatism and Conductionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to anatomical changes, endurance training may also cause different functional changes, such as arrhythmias and abnormalities in atrioventricular conduction. Sinus bradycardia is often affiliated with increased vagal activity, but can also be related to intrinsic electrophysiological adaptations of sinus node automaticity (Stein et al 2002).…”
Section: Hrv and Endurance Trainingmentioning
confidence: 99%
“…The present study also indicates alterations in the autonomic control of the heart as it was evident by HRV analysis. However, similar type of studies on animals and humans involving autonomic blockade have related the resting bradycardia to reduced intrinsic heart rate [10,13].…”
Section: Discussionmentioning
confidence: 99%